Changes in the functional capabilities of the cardiovascular system of medical students during the academic year - Brusov, M.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to analyse changes in the functional capabilities of the cardiovascular system of medical students during the academic year. Methods and structure of the study. The study was conducted at the Department of Physical Education of Surgut State University. To assess the functional capabilities of the cardiovascular system of students, the following were used: the Kerdov vegetative index (VI), the Robinson index (RI), the endurance coefficient (EC), and the cardiovascular system adaptation potential index. First-year medical students (103 in total, including 69 women and 34 men) took part in the testing. Results and conclusions. An analysis of changes in the functional capabilities of the cardiovascular system of medical students during the academic year revealed a positive trend in indicators. Young men showed economisation of cardiac activity, while young women showed stabilisation of regulatory processes. The results obtained reflect the formation of adaptive mechanisms in the bodies of first-year students.